Advanced Private Banking in Terms of Ecology - Nowak, Kamil (Copernican Journal of Finance & Accounting, 2014)
In recent years it has been observed that financial institutions have become aware of the social responsibility of businesses and in particular, the attention has been drawn to ecology. The purpose of this paper is to present the highest, third level of involvement of financial institutions in Ecology. Paper looks into sustainable investing through private banking sector. Financial institutions analyzed in this paper were chosen due to exquisite approach to the environment protection. The article analyses the advanced and innovative solutions introduced by private banking for the benefit of the protection of natural surroundings.